Membumikan Nilai dan Etika Politik Kristen dalam Teologi Titus 3:1-7 bagi Politikus Kristen Masa Kini - Yonathan Salmon Efrayim Ngesthi; Yonatan Alex Arifianto; Nining Indriana (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2024)
Many people of God feel reluctant or unwilling to discuss political ethics. Moreover, when Christians talk about politics, they will unilaterally stay away from it.  Because there is an assumption that Christianity should not be mixed with politics. Through this research, Christian politicians who are involved in politics can ground the values and ethics of Christian politics in the theology of Titus 3:1-7 for today's Christian politicians as a basis for building healthy political theological ethics. Using a descriptive qualitative method with a literature study approach, it can be concluded that grounding Christian political values and ethics in the theology of Titus 3:1-7 for today's Christian politicians requires an understanding and paradigm that Christian politicians can know the nature of politics and its interests. They can even understand the church and political challenges. So that politicians who live with integrity have attitudes and principles that are in accordance with Christian political values and ethics. Of course, Christian politicians must submit to the government and the law, which is to bring obedience in doing good deeds, not slander, not quarrel and be able to live in obedience. Not going astray, not being a slave to lust, not living in wickedness, not living in malice and hatred and certainly being able to appreciate grace. AbstrakBanyak umat Tuhan yang merasa sungkan atau tidak mau untuk membahas etika politik. Apalagi adanya orang Kristen bila berbicara tentang politik maka secara sepihak akan menjauhi hal tersebut.  Karena adanya anggapan bahwa kekristenan tidak boleh dicampuradukan dengan politik. Melalui penelitian ini maka politikus Kristen yang terjun dalam percaturan politik dapat membumikan nilai dan etika politik Kristen dalam teologi Titus 3:1-7 bagi politikus Kristen masa kini sebagai dasar dalam membangun etika teologis politik yang sehat. Menggunakan metode kualitatif deskriptif dengan pendekatan studi literatur maka dapat disimpulkan membumikan nilai dan etika politik Kristen dalam teologi Titus 3:1-7 bagi politikus Kristen masa kini, diperlukan pengertian dan paradigma bahwa politikus Kristen dapat mengetahui hakikat politik dan kepentingannya. Bahkan mereka dapat memahami gereja dan tantangan politik. Supaya politikus yang hidup berintegritas memiliki sikap dan prinsip yang sesuai dengan nilai dan etika politik Kristen. Tentunya politikus Kristen harus tunduk kepada pemerintah dan hukum, yang memang untuk membawa ketaatan dalam melakukan perbuatan baik, tidak memfitnah, tidak bertengkar dan dapat hidup dalam Ketaatan. Tidak Sesat, tidak menjadi budak hawa nafsu, tidak hidup dalam kejahatan, tidak hidup dalam kedengkian dan keji serta kebencian dan tentunya dapat menghargai kasih karunia.